THE INFLUENCE OF JOB INSECURITY, WORKLOAD, AND JOB STRESS ON TURNOVER INTENTION AMONG EMPLOYEES AT HERMINA HOSPITAL SUKABUMI - Novita Badra Fitriani; Tetty Suffianty Zafar; R Deni Muhammad Danial (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This study investigates the effect of job insecurity, workload, and job stress on turnover intention among employees at Hermina Hospital Sukabumi. The rising turnover rate in the healthcare sector, especially in hospitals like Hermina, which has surpassed its organizational turnover target of 6%, has raised concerns regarding employee retention and organizational sustainability. Turnover intention is a critical issue as it often leads to higher recruitment costs, loss of experienced personnel, and decreased service quality, particularly in healthcare settings where employee consistency is vital. Therefore, understanding the underlying psychological and organizational factors influencing turnover intention becomes essential. This research applies a quantitative approach with a survey method to examine the relationship between job insecurity, workload, and job stress with turnover intention. Data were collected from 80 employees using a structured, closed-ended questionnaire and analyzed through multiple linear regression using SPSS software. The theoretical framework integrates concepts from human resource management, organizational behavior, and psychological stress theory. The findings reveal that job insecurity and workload positively and significantly influence turnover intention, meaning that employees who perceive instability in their jobs and experience high work demands are more likely to consider leaving the organization. Interestingly, job stress shows a negative yet significant effect, implying that stress, although present, might lead to adaptation rather than resignation. This unexpected result suggests that not all stress is detrimental, and some employees may develop coping mechanisms that allow them to remain in their roles. Overall, the study emphasizes the importance of managerial strategies to enhance job stability and maintain balanced workloads in hospital environments. It also calls attention to the nuanced role of stress, advocating for workplace support systems that help employees manage pressure without triggering withdrawal behaviors. This research contributes valuable insights into employee retention efforts within Indonesia’s healthcare industry.